Lexical Peculiarities of Belarusian Russian Independent from the Influence of the Belarusian Language - Goritskaya, Olga (Respectus Philologicus, 2018)
[full article, abstract in Russian; abstract in English]The article focuses on the interaction of external and internal factors in language change. The paper deals with lexical units that have emerged in the Belarusian variety of Russian without the direct influence of the Belarusian language. The author analyses lexemes derived from Russian morphemes, new meanings of Russian words, and multi-word nominative units, including periphrasis. These items represent how the potential of the Russian language system is realized.The study shows that regionally specific lexical units denote both culture-bound and universal phenomena. The emergence of the units from the latter category is caused by the lexical modernization that may take different forms in different regions. In addition, there is an intermediate group of lexical units: they are not culture-bound but their formation is related to the facts relevant to Belarus. Some lexical units are allusive and refer to political speeches and other famous texts.
Keywords: The Belarusian Variety of the Russian Language, Belarusian-Russian, Pluricentric Language, Non-dominant Variety of a Pluricentric Language, Lexical Variation